Tobacco smoking during pregnancy: Women’s perception about the usefulness of smoking cessation interventions - Almeida, Rita (2022)
Tobacco consumption during pregnancy is a serious public health problem due to its negative effects on fetal development and on pregnant women’s health and well-being. Thus, it is of utmost importance to plan and implement smoking cessation interventions, to prevent the negative impact of this risk factor, namely on children’s health and development. This cross-sectional study aimed at exploring the perceptions and beliefs about the usefulness of smoking cessation interventions during pregnancy, in a sample of pregnant Portuguese women. The smoking use by pregnant women, as well as the risk factors associated with tobacco smoking during pregnancy, were also analyzed. The sample included 247 pregnant Portuguese women aged between 18–43-years-old (M = 30.30, SD = 5.02): 42.5% never smoked, 18.3% quit smoking before pregnancy, 19.0% quit smoking after getting pregnant and 20.2% were current smokers. The pregnant Portuguese women who smoked during pregnancy (current smokers or who quit smoking after getting pregnant) were mostly single or divorced, with lower education levels, showed a higher prevalence of clinically significant anxiety symptoms, and perceived smoking cessation interventions during pregnancy as less useful when compared to women who never smoked or quit smoking prior pregnancy. Daily or weekly smoking cessation interventions, implemented by health professionals such as doctors, nurses, or psychologists are the ones perceived as the most useful for pregnant women. These findings provide important clues for the planning of smoking cessation interventions during pregnancy, highlighting the domains that should be carefully monitored by health professionals. Specific strategies should also be used by health professionals to promote smoking cessation considering the demands of pregnancy and postpartum.